Pitch your way to success / Assoc. Prof. Dr. Shariza Sahudin - Sahudin, Shariza (Faculty of Pharmacy, 2023)
Traditionally, teaching and research have been the main missions of a university. However, this has changed with increased globalisation, reduced funding, and new perspectives on the role of the university in the system of knowledge production which is seen currently. Innovation is increasingly seen as an evolutionary process that involves different institutional spheres and sectors in our society. The Malaysian Government has recognized the importance of our higher education sector through its collaboration with industries which aims to promote innovation. Various forms of MoU/MoA in areas of staff mobility, supervision, product development, commercialization and technology transfer at local and international levels are implemented in the aim to promote and inculcate an ecosystem-based innovation through R&D. These are implemented in the hope of commercialising the innovation either in the form of product licensing agreements, start-up or spin off companies from the university.